STRATEGI KOMUNIKASI KRISIS DINAS KOMINFO KOTA KEDIRI DALAM MENAGGULANGI DISINFORMASI COVID 19 - Amalia Rosyadi Putri; Abdulah abdulah (Al-Tsiqoh : Jurnal Ekonomi dan Dakwah Islam, 2021)
The Covid-19 pandemic continues to this day. Information broadcasts in various mass media are still busy discussing the corona virus, including the Kediri City mass media. The amount of information scattered in the mass media does not fully guarantee valid news. The Department of Communications and Informatics as a government agency in charge of managing information, should have taken a preventive step to deal with the occurrence of disinformation in the mass media of Kediri City. With valid information, it is easier for people to receive real information and regardless of being skeptical of information in the mass media. This research is a qualitative research, using a phenomenological approach with the social construction theory of Peter L. Berger and Thomas Luckmann. The results of the research, crisis communication strategies, namely: (1) Establishing a Covid-19 Task Force Team for the City of Kediri, (2) Creating a special channel/social media about information on handling Covid-19 in the City of Kediri, (3) Every day the Kominfo Service will update data on online media, waiting for data from the Health Office, (4) Disseminating large-scale billboards/banners, (5) Cooperating with various institutions and local residents. In collaboration with the press agency (print media) of the City of Kediri.